The extraditability of corruption offenders: An analytical study in light of international law and national legislations - Malaa, Mouna (The International tax journal, 2025)
The extradition of corruption offenders constitutes one of the mechanisms of international judicial cooperation in the fight against corruption. However, its practical implementation faces numerous legal and procedural challenges, such as the divergence in the legal characterization of corruption among national systems, the existence of extradition bars due to the political nature of the offense, and the absence of the principle of dual criminality between the requesting and the requested states. This study aims to clarify the legal and theoretical frameworks of extradition and to identify the key general principles governing it. Additionally, it analyzes the legal nature of corruption offenses in order to determine their classification among extraditable crimes. The study concludes that corruption offenses are indeed subject to extradition, provided that the conditions for such a procedure are met and in the absence of any contrary provision in bilateral agreements.